Early versus delayed enteral nutrition support for critically ill adults - Fuentes Padilla, Paulina (Cochrane Database Syst Rev, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To evaluate the efficacy and safety of early (within 48 hours) versus delayed enteral nutrition (after 48 hours) in critically ill adults.